2012
DOI: 10.1111/j.1524-4725.2011.02298.x
|View full text |Cite
|
Sign up to set email alerts
|

Periorbital Rejuvenation with Fractional 1,550-nm Ytterbium/Erbium Fiber Laser and Variable Square Pulse 2,940-nm Erbium:YAG laser in Asians: A Comparison Study

Abstract: Fractional Yb/Er fiber and VSP Er:YAG lasers are effective in improving periorbital wrinkles in Asians, with minimal side effects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
0

Year Published

2014
2014
2025
2025

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 29 publications
1
19
0
Order By: Relevance
“…In 2012, Wattanakrai, Pootongkam and Rojhirunsakool compared the methods in periorbital wrinkles of 22 patients, and suggested that they were equivalent. 21 Parameters were similar to those we proposed in our study but no histologic observation was performed. Again in 2012, Bas and colleagues published the first histological comparison between these methods.…”
Section: Introductionsupporting
confidence: 85%
“…In 2012, Wattanakrai, Pootongkam and Rojhirunsakool compared the methods in periorbital wrinkles of 22 patients, and suggested that they were equivalent. 21 Parameters were similar to those we proposed in our study but no histologic observation was performed. Again in 2012, Bas and colleagues published the first histological comparison between these methods.…”
Section: Introductionsupporting
confidence: 85%
“…30 In another study, 55% of patients displayed moderate to excellent improvement after three serial treatments. 40 Because eyelid skin is very thin, high energies are not required to achieve effective skin tightening in this area, even with a nonablative device. A series of treatments is recommended for optimal results.…”
Section: Clinical Data On Periorbital Resurfacing or Tighteningmentioning
confidence: 99%
“…Eyelid skin is the thinnest in the body . Presently, there are many optional procedures for treating periorbital wrinkles, such as applying topical drugs with retinoids, chemical peeling with glycolic or trichloroacetic acid, microdermabrasion, botulinum toxin, filler injection, laser, nonlaser method, and surgery . Nevertheless, there is currently no standard treatment.…”
Section: Introductionmentioning
confidence: 99%